Improving STING agonist-based cancer therapy by inhibiting the autophagy-related protein VPS34 - Elisabetta Bartolini; Kris Van Moer; Bassam Janji (OncoImmunology)
We have recently demonstrated that inhibiting VPS34 enhances T-cell-recruiting chemokines through the activation of the cGAS/STING pathway using the STING agonist ADU-S100. Combining VPS34 inhibitors with ADU-S100 increased cytokine release and improved tumor control in mouse models, suggesting a potential synergy between VPS34 inhibition and therapies based on STING agonists.